Transcranial Direct Current Stimulation in Tinnitus Patients: A Systemic Review and Meta-Analysis - Jae-Jin Song; Sven Vanneste; Paul Van de Heyning; Dirk De Ridder (The Scientific World Journal)
Although transcranial direct current stimulation (tDCS) has already been used to manage tinnitus patients, paucity of reports and variations in protocols preclude a comprehensive understanding. Hence, we conducted a meta-analysis based on systemic review to assess effectiveness of tDCS in tinnitus management and to compare stimulation parameters. PubMed was searched for tDCS studies in tinnitus. For randomized controlled trials (RCTs), a meta-analysis was performed. A total of 17 studies were identified and 6 of them were included in the systemic review and 2 RCTs were included in the meta-analysis. Overall 39.5% responded to active tDCS with a mean tinnitus intensity reduction of 13.5%. Additionally, left temporal area (LTA) and bifrontal tDCS indicated comparable results. Active tDCS was found to be more effective than sham tDCS for tinnitus intensity reduction (Hedges' g=.77, 95% confidence interval 0.23–1.31). The efficacy of tDCS in tinnitus could not be fully confirmed by the current study because of the limited number of studies, but all studies included in the current systemic review and meta-analysis demonstrated significant tinnitus intensity improvement. Therefore, tDCS may be a promising tool for tinnitus management. Future RCTs in a large series regarding the efficacy as well as the comparison between LTA- and bifrontal tDCS are recommended.